2013
DOI: 10.1002/ejoc.201301015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Fungal Lipo‐Chitooligosaccharide Myc‐IV (C16:0, S), Symbiotic Signal of Arbuscular Mycorrhiza

Abstract: A new synthesis of the fungal lipo‐chitooligosaccharide Myc‐IV (C16:0, S), which was recently reported to be a major symbiotic signalling molecule in arbuscular mycorrhiza, is described. Key steps include the oxidative cleavage of a 4,6‐O‐benzylidene acetal to prepare a disaccharidic glycosyl acceptor, and stereoselective glycosylations with 2‐methyl‐5‐tert‐butylphenyl thioglycosyl donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…At this stage, HPLC‐MS analysis showed that the Cbz (benzyloxycarbonyl) group survived the two steps. For comparison, the analogous tetrasaccharide lacking an ITag (i.e., 23 ) gave, without complication, chitotetrasaccharide 24 in 84 % yield, as reported previously18a (Table 2, entry 3). Furthermore, monosaccharide 10a was transformed into ITagged N ‐acetyl glucosamine derivative 21 , which was easily purified by simple organic solvent washes (82 % yield; Table 2, entry 2).…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…At this stage, HPLC‐MS analysis showed that the Cbz (benzyloxycarbonyl) group survived the two steps. For comparison, the analogous tetrasaccharide lacking an ITag (i.e., 23 ) gave, without complication, chitotetrasaccharide 24 in 84 % yield, as reported previously18a (Table 2, entry 3). Furthermore, monosaccharide 10a was transformed into ITagged N ‐acetyl glucosamine derivative 21 , which was easily purified by simple organic solvent washes (82 % yield; Table 2, entry 2).…”
Section: Resultssupporting
confidence: 80%
“…We chose to attach the ITag to the glycosyl acceptor with a linker derived from 4 or 5 (Scheme ) connected to the C‐1 position by a stable benzyl glycoside linkage, and removable by hydrogenolysis 13b,17a,17c,20. Glycosylation of benzyl alcohol 4 with donor 3 18a prepared from the nonmalodorous 2‐methyl‐5‐ tert ‐butylphenylthiol (HSMbp),21 followed by halide displacement at the benzylic position provided ITagged glycosyl acceptor precursor 6 in moderate yield (44 %) 22. This sequence was preferred over direct glycosylation of a benzyl alcohol already bearing the ITag23 (viscous liquid) for practical reasons, even though the overall yield was similar.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations